PENGARUH PEMBELAJARAN NUMERASI TERHADAP KEMAMPUAN MENYELESAIKAN MASALAH MATEMATIKA SISWA KELAS IV SDN RUNGKUT MENANGGAL I SURABAYA - Ainanda, Dimas Agung; Hidayat, Muhammad Thamrin; Hartatik, Sri; Nafiah, Nafiah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The purpose of this study is to analyze the effect of learning numeracy on the ability to solve mathematical problems. Polya’s problem solving steps consist of understanding the problem, planning a solution, carrying out a solution plan, and checking again. This type of research is to use quantitative research methods and use pretest and posttest data collection techniques. The population in this study were fourth grade students at Rungkut Menggal I Elementary School in Surabaya, totaling 30 students. The result of this research is that there is a difference in the effect of learning mathematics numeracy for fourth grade students at Rungkut Menggal I Elementary School in Surabaya. This can be seen from the results of testing the hypothesis using the t-test, it is found that the value of Tcount > Ttable is 5.038 > 2.048. Thus it can be concluded that Ho is rejected and H1 is accepted, meaning that there is an effect of learning mathematical numeracy on problem solving.